Organic reaction mechanisms: selected problems and solutions - Groutas, William C (New York, John Wiley Sons, Inc., 2000)
This hands--on manual allows readers to gain a better understanding of organic reaction mechanisms by solving a wide range of problems. Answers for the problems are included along with mini--reviews that summarize and emphasize fundamental principles. This approach sharpens readersa reasoning ability and critical thinking.
Glossary 3p.
Keywords: Chemical reactions; Organic compounds; Chemistry